A study in the correlation between hammer throw and weight throw performance and development for U.S. collegiate throwers - Babbitt, D. G. (International Journal of Coaching Science, 2017)
Performance results of three hundred and two (151 men and 151 women) collegiate hammer/weight throwers were analyzed to determine the correlation be between hammer throw and weight throw performance. Statistical analysis showed a significant correlation between hammer and weight throw performance for both genders (r=.7521, p<.001 for men, and r=.5219, p<.001 for women). Results for both genders were scrutinized to see how closely they followed a theoretical correlation, in which the slope is y=x, and r=1, where hammer throw performance in meters (x) will equal weight throw performance measured in feet (y). Results suggest that the trend lines generated by actual performance data show a strong correlation between collegiate male hammer throw and weight performances that more closely resembles the theoretical trend line when compared with that for collegiate female hammer/weight throwers.